SHARE: An ethical framework for equitable data sharing in Caribbean health research - Michael H. Campbell; Natalie S. Greaves (Revista Panamericana de Salud Pública)
Data sharing increasingly underpins collaborative research to address complex regional and global public health problems. Advances in analytic tools, including machine learning, have expanded the potential benefits derived from large global repositories of open data. Participating in open data collaboratives offers opportunities for Caribbean researchers to advance the health of the region’s population through shared data-driven science and policy. However, ethical challenges complicate these efforts. Here we discuss fundamental challenges that threaten to impede progress if not strategically addressed, including power dynamics among funders and researchers in high-income countries and Caribbean stakeholders; research and health equity; threats to privacy; and risk of stigma. These challenges may be exacerbated by resource and infrastructure limitations often seen in small island developing states (SIDS) and low- and middle-income countries. We propose a framework for Safeguarding Health And Research data sharing by promoting Equity (SHARE) for Caribbean researchers and communities participating in shared data science. Using the SHARE framework can support regionally relevant and culturally responsive work already underway in the region and further develop capacity for intentional sharing and (re)use of Caribbean health data.